1981
DOI: 10.1093/oxfordjournals.aje.a113111
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant-Associated Type a Botulism: Transmission by Potato Salad

Abstract: In the period November 13-18, 1978, seven cases of type A botulism occurred in persons who had eaten in a restaurant in Colorado. The outbreak was recognized when two persons who had independently eaten at the restaurant were hospitalized with an illness compatible with botulism. Surveillance efforts identified five additional cases. Potato salad made at the restaurant and available for service during an 11-day period was epidemiologically incriminated as the vehicle of botulinal toxin transmission (p less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Washington and Oregon rank third and fourth in outbreaks, respectively, almost exclusively type A. Four large outbreaks occurred in restaurants during this period, due to home-type processed peppers (TERRANOVA et al 1978), potato salad (SEALS et al 1981;MANN et al 1982), and cooked onions (MACDoNALD et al 1985).…”
Section: Foodborne Botulismmentioning
confidence: 90%
“…Washington and Oregon rank third and fourth in outbreaks, respectively, almost exclusively type A. Four large outbreaks occurred in restaurants during this period, due to home-type processed peppers (TERRANOVA et al 1978), potato salad (SEALS et al 1981;MANN et al 1982), and cooked onions (MACDoNALD et al 1985).…”
Section: Foodborne Botulismmentioning
confidence: 90%
“…C. botulinum is commonly found in the soil, and its spores have been found on raw potatoes (5). Several outbreaks of botulism caused by eating potatoes have occurred in the United States (6)(7)(8), and laboratory studies have shown that C. botulinum spores on the surface of raw potatoes can survive baking and lead to production of botulinum toxin (5). The warm anaerobic fermentation process of making pruno probably predisposes toward production of botulinum toxin, particularly if any ingredient happens to be contaminated with C. botulinum or its spores, such as the potatoes used in these 2 instances.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the epidemiologic evidence that pruno containing a potato was the source of the outbreak. Potatoes have been commonly associated with botulism [24][25][26], and pruno containing a potato is now a well-recognized cause of botulism. Whole potatoes, one of the few nonprocessed foods served at prisons, have been banned at prison A as a result of this outbreak.…”
Section: Continuedmentioning
confidence: 99%